If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y(y + 12) = y + -9 Reorder the terms: -2y(12 + y) = y + -9 (12 * -2y + y * -2y) = y + -9 (-24y + -2y2) = y + -9 Reorder the terms: -24y + -2y2 = -9 + y Solving -24y + -2y2 = -9 + y Solving for variable 'y'. Reorder the terms: 9 + -24y + -1y + -2y2 = -9 + y + 9 + -1y Combine like terms: -24y + -1y = -25y 9 + -25y + -2y2 = -9 + y + 9 + -1y Reorder the terms: 9 + -25y + -2y2 = -9 + 9 + y + -1y Combine like terms: -9 + 9 = 0 9 + -25y + -2y2 = 0 + y + -1y 9 + -25y + -2y2 = y + -1y Combine like terms: y + -1y = 0 9 + -25y + -2y2 = 0 Begin completing the square. Divide all terms by -2 the coefficient of the squared term: Divide each side by '-2'. -4.5 + 12.5y + y2 = 0 Move the constant term to the right: Add '4.5' to each side of the equation. -4.5 + 12.5y + 4.5 + y2 = 0 + 4.5 Reorder the terms: -4.5 + 4.5 + 12.5y + y2 = 0 + 4.5 Combine like terms: -4.5 + 4.5 = 0.0 0.0 + 12.5y + y2 = 0 + 4.5 12.5y + y2 = 0 + 4.5 Combine like terms: 0 + 4.5 = 4.5 12.5y + y2 = 4.5 The y term is 12.5y. Take half its coefficient (6.25). Square it (39.0625) and add it to both sides. Add '39.0625' to each side of the equation. 12.5y + 39.0625 + y2 = 4.5 + 39.0625 Reorder the terms: 39.0625 + 12.5y + y2 = 4.5 + 39.0625 Combine like terms: 4.5 + 39.0625 = 43.5625 39.0625 + 12.5y + y2 = 43.5625 Factor a perfect square on the left side: (y + 6.25)(y + 6.25) = 43.5625 Calculate the square root of the right side: 6.600189391 Break this problem into two subproblems by setting (y + 6.25) equal to 6.600189391 and -6.600189391.Subproblem 1
y + 6.25 = 6.600189391 Simplifying y + 6.25 = 6.600189391 Reorder the terms: 6.25 + y = 6.600189391 Solving 6.25 + y = 6.600189391 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6.25' to each side of the equation. 6.25 + -6.25 + y = 6.600189391 + -6.25 Combine like terms: 6.25 + -6.25 = 0.00 0.00 + y = 6.600189391 + -6.25 y = 6.600189391 + -6.25 Combine like terms: 6.600189391 + -6.25 = 0.350189391 y = 0.350189391 Simplifying y = 0.350189391Subproblem 2
y + 6.25 = -6.600189391 Simplifying y + 6.25 = -6.600189391 Reorder the terms: 6.25 + y = -6.600189391 Solving 6.25 + y = -6.600189391 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6.25' to each side of the equation. 6.25 + -6.25 + y = -6.600189391 + -6.25 Combine like terms: 6.25 + -6.25 = 0.00 0.00 + y = -6.600189391 + -6.25 y = -6.600189391 + -6.25 Combine like terms: -6.600189391 + -6.25 = -12.850189391 y = -12.850189391 Simplifying y = -12.850189391Solution
The solution to the problem is based on the solutions from the subproblems. y = {0.350189391, -12.850189391}
| a(11)=2-6(11-1) | | x+(.08x)=18.90 | | k/2=2 | | 8x-6x^2-8=0 | | X^6-37=0 | | 8x-6=5x-4.5 | | 11.20x+10.20y=428 | | X^4+x^2-2= | | w-11=2 | | 6y-x+7=0 | | 12a-2(5a-4)= | | 13=-4d | | 8x-41=180 | | -45-3v=-66 | | -7/10=x/10 | | 5x(3x+9)=0 | | 8x+41=180 | | 16/3=m/3 | | c-14=5 | | 7x=4y-5 | | -9=n+6 | | 3=j/3 | | 6=3h | | .3h=15 | | 27-8p=123 | | 27-8p=23 | | 15x+14=18x+5 | | r-1=5 | | 26-8p=123 | | 18a-10=8a+20 | | 10y=3y+7 | | 20c+14=19c+17 |